The effects of unemployment on juvenile offending - Fergusson, David (Criminal behaviour and mental health, 1997)
This study examined the associations between duration of unemployment and a series of measures of young offending in a birth cohort of New Zealand children studied to the age of 18 years. Increasing duration of unemployment was significantly P <0.001 associated with a series of measures of young offending including: violent offending, property offending, arrests and convictions. Specifically, young people who had been unemployed for six months or longer had higher mean levels of offending and rates of property offending, violent offending, arrest and conviction that were 3.0 to 10.4 times higher than those of young people who had not been unemployed. However, unemployment was also associated with a range of adverse social, family, school, individual and related factors. When the associations between unemployment and criminal offending were adjusted for a range of measures assessed prior to school leaving age these associations were substantially reduced. However, even after adjustment for these factors young people exposed to unemployment had significantly P <0.05 higher mean levels of property and violent offending and significantly P <0.05 higher rates of recurrent property offending, arrest and conviction. It is concluded that much of the association between unemployment and juvenile crime is likely to reflect common life course processes and factors that make young people vulnerable to both unemployment and criminal offending. However, exposure to unemployment following school leaving may be associated with increased risks of juvenile offending, and particularly property offending. Copyright Ř 1997 Whurr Publishers Ltd